The Contrasting Footprint of Labour and Capital in Post‐colonial India - Breman, Jan (Development and change, 2024)
ABSTRACT India's struggle for independence held the promise of an end to poverty and redemption from the communal‐cum‐class‐based inequality which had kept the peasant economy backward. But the planned substitution of the agrarian‐rural fabric for an industrial‐urban way of life failed to materialize. Casualization and contractualization of waged work indicated that labour had become thoroughly commodified in a state of ongoing footlooseness. It was a proletarianization which did not allow for the collective action precondition to raise and settle the social question. The onslaught of neoliberal capitalism in the last quarter of the 20th century ended the brokerage of the nation state to secure the interests of labour next to those of capital. Less than 10 per cent of the workforce has continued to enjoy formalized occupational engagement, mainly in the downgraded public economy. Corporate capital in collusion with statist autocracy has not only effectuated the deregulation of employment but also abandoned the legal code of formality. The outcome is a state of lawlessness for the people at the bottom of the pile. Besides big business, politics and governance are identified in this reconfiguration as stakeholders in a brutal regime of informality, erosive of equality, democracy, welfare and civil rights.